Pericarp starch metabolism is associated with caryopsis development and endosperm starch accumulation in common wheat. (May 2023) - Zhuo, Jiahui; Wang, Ke; Wang, Ning; Xing, Caihong; Peng, Da; Wang, Xinyu; Qu, Ge; Kang, Caiyun; Ye, Xingguo; Li, Yaxuan; Yan, Yueming; Li, Xiaohui
Abstract: The wheat pericarp is the main component of the caryopsis at the early development stage and ultimately converts into a tissue that covers the mature caryopsis. A large number of starch granules are accumulated in the pericarp, but the production of and the role of starch granules in caryopsis development remain- elusive. In the present study, the relationship between accumulated starch granules and starch metabolism-related genes in wheat pericarp was investigated using paraffin section observations, expression analysis, and mutant analysis. Starch synthesis is initiated before anthesis and is dependent on a sucrose uptake and conversion system similar to that in the endosperm. TaPTST2 is required to initiate the production of pericarp starch granules. Pericarp starch granules gradually disappeared at the filling stage with high expression levels of genes encoding β-amylase, sucrose-phosphate synthase, and sucrose-phosphate phosphatase. As a maternal tissue adjacent to the endosperm and embryo, the pericarp plays a temporary reservoir for excess nutrients delivered into the caryopsis during the early development stage and exported at the filling stage. The pericarp contributes to the development of the endosperm and embryo as well as the accumulation of endosperm starch. The metabolism of pericarp starch may affect the weight of the wheat caryopsis. Highlights: Pericarp cell possesses a complete starch metabolism system. TaPTST2 promotes the initiation of pericarp starch granule. Pericarp acts as a temporary reservoir for nutrients delivered into the young caryopsis.